2017
DOI: 10.1080/19476337.2017.1327461
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pomegranate seed flour on dough rheology and bread quality

Abstract: The objective of this study was to determine the effects of pomegranate seed flour (PSF) on dough and bread quality. PSF with 15.66% protein, 18.24% lipid, 52.22% dietary fiber, 40.60 g/kg GAE total phenolic and 1049.10 IC50 = μg/ml antiradical activity was substituted for bread wheat flour at 0%, 5%, 7.5% and 10% levels. While 5% PSF did not show any significant effect on water absorption, stability and pressure increased and development time and extensibility decreased as addition level increased. With the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
3
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 49 publications
1
13
3
2
Order By: Relevance
“…PSP showed a total phenolic content (TPC) value of 73.8 ± 0.5 mg gallic acid equivalent (GAE)/g. This result is higher than those reported for pomegranate peel extracts obtained from the co-product of juice extraction with TPC values of 54.54 [38] and 19.30 mg GAE/g [24], and pomegranate seed flower with TPC of 40.60 mg GAE/g [32], respectively. However, a TPC value of 81.15 mg GAE/g was reported by Harini et al from pomegranate peel ethanolic extracts [39].…”
Section: Sulfuric Hydrolysiscontrasting
confidence: 73%
See 1 more Smart Citation
“…PSP showed a total phenolic content (TPC) value of 73.8 ± 0.5 mg gallic acid equivalent (GAE)/g. This result is higher than those reported for pomegranate peel extracts obtained from the co-product of juice extraction with TPC values of 54.54 [38] and 19.30 mg GAE/g [24], and pomegranate seed flower with TPC of 40.60 mg GAE/g [32], respectively. However, a TPC value of 81.15 mg GAE/g was reported by Harini et al from pomegranate peel ethanolic extracts [39].…”
Section: Sulfuric Hydrolysiscontrasting
confidence: 73%
“…The chemical composition obtained for PSP showed humidity, ash and fat contents of 4.51 ± 0.25, 1.82 ± 0.12 and 16.26 ± 0.37 g/100 g, respectively. Higher contents were obtained by Gül andŞen when studying the potential of pomegranate seed flour (PSF) as a functional ingredient in wheat bread [32], reporting values of 10.67% for moisture, 3.21% for ash, and 18.24% for total lipid contents in PSF. These differences could nevertheless be expected since PSP is the result of the mixture of pressed seed and arils and not only seeds and, therefore, compositions should be different.…”
Section: Psp Characterizationmentioning
confidence: 95%
“…Since the other ingredients were same in all experiments, the change in %PSP fraction and peanuts had shown a significant effect on all sensory attributes and overall quality of the products, this may be due to the granular texture of peanuts and powdered PSP fraction which might cause variations in the degree of color, surface stickiness, hardness, crunchiness, and other parameters which are directly related to the overall quality of the product. Similar studies conducted by Gül and Şen () with the addition of Pomegranate Seed Flour (PSF) to the bread revealed that PSF enriched breads had significantly low sensory quality when compared with control. Addition of PSP at above 10% level to the bread showed lower sensory quality attributes (Bourekoua et al, ).…”
Section: Discussionsupporting
confidence: 55%
“…Çam, Erdoğan, Aslan, and Dinç (2013) developed an ice-cream with replacement of milk fat with PSO showed increase in the conjugated fatty acid content and also the recovery of the PSO. Similarly, incorporation of 0.5% (w/w) PSP extracts in beef and chicken meat balls which were processed at high temperature, the prepared products were found to be devoid of heterocyclic aromatic amines, thus may provide a safer product (Keşkekoğlu & Üren, 2014 Gül and Şen (2017) with the addition of Pomegranate Seed Flour (PSF) to the bread revealed that PSF enriched breads had significantly low sensory quality when compared with control. Addition of PSP at above 10% level to the bread showed lower sensory quality attributes (Bourekoua et al, 2018).…”
Section: F I G U R Ementioning
confidence: 99%
“…Bread is a staple food in many countries, constituting a valuable source of energy and many important nutrients for the proper functioning of the body (Różyło, 2014). Till date, many studies have been published with regard to the improvement of nutraceutical properties of a bread via enrichment (Dziki, Różyło, Gawlik-Dziki, & Świeca, 2014;Gül & Şen, 2017;Xiao et al, 2016). Breads with high concentrations of antioxidants are especially in great demand because of their beneficial role in the maintenance and enhancement of health and protection against many diseases (Sivam, Sun-Waterhouse, Waterhouse, Quek, & Perera, 2011).…”
Section: Introductionmentioning
confidence: 99%